TAX AVOIDANCE IN INDONESIAN COMMERCIAL BANKS: POLITICAL CONNECTIONS AND BOARD OF COMMISSIONERS - Rahayu, Faza Lutfi; Pratama, Bima Cinintya; Fitriati, Azmi; Santoso, Selamet Eko Budi (Universitas Muhammadiyah Metro Lampung, 2023)
The purpose of this research is to test tax avoidance taking into account the influence of political connections, as well as tenure of the board of commissioners and compensation of the board of commissioners as moderating variables. The population used in this study are commercial banks registered with the Financial Services Authority (OJK) with a sample of 205 out of a total of 41 banking sector companies in 2017-2021. This study uses panel data regression model analysis. The analysis techniques used in this study were descriptive statistical tests, preliminary tests ( Breusch-Pagan, likelihood tests, Hausman tests ), diagnostic tests (heteroscedasticity tests and autocorrelation tests), and hypothesis testing. Based on the results of the three preliminary tests in determining the panel data regression model, this study uses a random effect model to test the relationship between variables in model 1 and model 2 to test the hypothesis. The results of this study indicate that political connections have a negative effect on tax avoidance, meaning that the board of commissioners who have political connections does not change the characteristics of their special relationship with the government to always pay taxes according to the proper tax rate. The board of commissioners tenure variable has a positive effect on tax avoidance, this shows that the length of the term of office of members of the board of commissioners triggers more aggressive characteristics to take tax avoidance actions without looking at the risk-taker for the company as well as the reputation of the term of office as the board of commissioners. The Compensation variable of the board of commissioners has a positive effect on tax avoidance, this shows that giving compensation to members of the board of commissioners will reduce the level of profit after tax due to burdens or costs borne by the company. So what happens is the lower the taxable profit, the lower the effective tax charged. Meanwhile, this study can prove the role of the board of commissioner's tenure variable in strengthening the relationship between political connections and tax avoidance. Also, proving the role of the board of commissioner's compensation variable does not affect the relationship between political connections and tax avoidance.